La península Ibérica, el Atlántico y América. ¿Una etapa en el pasado de la globalización? - Joaquín Bosque Maurel (Anales de Geografía de la Universidad Complutense, 2002)
The geographical location of the Iberian Peninsula as a world crossroad, as a meeting point for Europe and Africa, for the Mediterranean sea and the Atlantic ocean, has implied a crossroad for physical features as web a complex historical evolution. It must be pointed out the early and century-long Spanish labor in the discovery and breakthrough of the Atlantic ocean and New World. Spanish positive or negative traces come up to nowadays. It is also a early and different version of globalization of world.